Evaluation of a simple fruit tree structural model - Láng, Z. (International Journal of Horticultural Science, 2009)
A simple three element tree structure model of Lang, 2006 was tested in plum orchard using two different inertia fruit tree shakers. The first was a slider crank type one; the second had rotating eccentric weights. The parameters of both were chosen to give similar frequency and amplitude output in average orchard conditions. Orchard experiments were carried out shaking the trees with both machines at several frequencies and shaking heights. The measured acceleration and amplitude values were plotted on diagrams together with the calculated acceleration and amplitude curves of the fruit tree-shaker machine model. Choosing the right fruit tree parameters, such as apparent spring constant, damping coefficient, reduced trunk mass and coefficient of elasticity of the trunk the measured and calculated values coincided well. This proves the ability of the fruit tree model for optimising the shaker parameters to any given orchard.